مكانة اللغة العربية والحالة الثقافية وبروز الأدب العربي في دولة تشاد: The Status of Arabic Language, the Cultural Situation, and the Emergence of Arabic Literature in the State of Chad - Ibrahim Kamsouloum Mahamat (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
مستخلص البحث: تكمن أهمية البحث في تحقيق غرضين أساسيين. الأول يتمثل في مكانة اللغة العربية والثقافة الاسلامية في المنطقة. والثاني يدور حول بروز الأدب العربي التشادي وأثره في نشر الثقافة العربية الاسلامية المتمثلة في وجود الممالك الاسلامية في تشاد. وتهدف الورقة إلى اظهار الدور الذي قام به الادباء التشاديون والعلماء التقليديون الذين بذلوا جهدا كبيرا في نشر الثقافة العربية والاسلامية عن طريق تلك المنظومات التي ألفوها والأشعار التعليمية التي تعد نقطة بداية لنشر العلوم حول منطقة حوض بحيرة تشاد. واتبع الباحث المنهج التحليلي الوصفي في دراسته لهذا الموضوع، وأخيرا تركزت الدراسة. في تناولها للمحاور الرئيسية الآتية: الحالة الثقافية الاسلامية ومظاهرها واللغة العربية ومكانتها وبروز الادب العربي الشادي، ثم خلاصة تشتمل على نتائج وتوصيات. الكلمات الأساسية: الثقافة، مكانة اللغة العربية، بروز الأدب العربي، دولة تشاد. Abstract: The importance of the research lies in achieving two basic purposes. The first is the status of the Arabic language and Islamic culture in the region. The second revolves around the emergence of Chadian Arabic literature and its impact on spreading Arab-Islamic culture represented by the presence of Islamic kingdoms in Chad. The paper aims to show the role played by Chadian writers and traditional scholars who made a great effort in spreading Arab and Islamic culture through the poems they composed and educational poems that are a starting point for spreading science around the Lake Chad Basin region. The researcher followed the descriptive analytical approach in his study of this topic, and finally the study focused on: It addresses the following main topics: the Islamic cultural situation and its manifestations, the Arabic language and its status, and the emergence of Shadi Arabic literature, then a summary that includes findings and recommendations. Keywords: Culture, Status of Arabic Languange, Emergence of Arabic Literature, State of Chad